2010
DOI: 10.2147/hiv.s11977
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis: pathogenesis and increased occurrence in individuals with HIV and Mycobacterium tuberculosis infection

Abstract: Atherosclerosis is a leading cause of coronary heart disease and stroke. Since 1981, more than 980,000 cases of AIDS have been reported in the United States. According to the Centers for Disease Control, more than 1 million Americans may be infected with HIV. By killing or damaging CD4+ T cells of the body’s immune system, HIV progressively destroys the body’s ability to fight infections. People diagnosed with AIDS often suffer from life-threatening diseases caused by opportunistic infections such as tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…TB and cardiovascular diseases have a close epidemiological and geographical overlap 36 . An important relationship has been demonstrated in the pathogenesis of TB and ASCVD 37 . The key hallmarks of atherosclerosis are LDL oxidation, foam cell formation and inflammation 38 .…”
Section: Discussionmentioning
confidence: 99%
“…TB and cardiovascular diseases have a close epidemiological and geographical overlap 36 . An important relationship has been demonstrated in the pathogenesis of TB and ASCVD 37 . The key hallmarks of atherosclerosis are LDL oxidation, foam cell formation and inflammation 38 .…”
Section: Discussionmentioning
confidence: 99%
“…TB and cardiovascular diseases have a close epidemiological and geographical overlap 31 . An important relationship has been demonstrated in the pathogenesis of TB and ASCVD 32 . A systematic review indicated that patients with TB have an increased risk of CAD 4 .…”
Section: Discussionmentioning
confidence: 99%